High Expression of BCL11A Predicts Poor Prognosis for Childhood MLL-r ALL - Wang, Lu-Lu; Yan, Dehong; Tang, Xue; Zhang, Mengqi; Liu, Shilin; Wang, Ying; Zhang, Min; Zhou, Guichi; Li, Tonghui; Jiang, Feifei; Chen, Xiaowen; Wen, Feiqiu; et al. (Frontiers in Oncology, 2021)
Background Despite much improvement in the treatment for acute lymphoblastic leukemia (ALL), childhood ALLs with MLL-rearrangement (MLL-r) still has inferior dismal prognosis. Thus, defining mechanisms underlying MLL-r ALL maintenance is critical for developing effective therapy. Methods GSE13159 and GSE28497 were downloaded via the Oncomine website. Differentially expressed genes (DEGs) between MLL-r ALLs and normal samples were identified by R software. Next, functional enrichment analysis of these DEGs were carried out by Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Set Enrichment Analysis (GSEA) and Search Tool for the Retrieval of Interacting Genes/Proteins (STRING). Then, the key hub genes and modules were identified by Weighted Gene Co-expression Network Analysis (WGCNA). Therapeutically Applicable Research to Generate Effective Treatments (TARGET) ALL (Phase I) of UCSC Xena analysis, RT-qPCR and Kaplan-Meier analysis were conducted for validation the expression of key hub genes from bone marrow cells of childhood ALL patients or ALL cell lines. Results A total of 1045 DEGs were identified from GSE13159 and GSE28497. Through GO, KEGG, GSEA and STRING analysis, we demonstrated that MLL-r ALLs were upregulating "nucleosome assembly" and "B cell receptor signal pathway" genes or proteins. WGCNA analysis found 18 gene modules using hierarchical clustering between MLL-r ALLs and normal. The Venn diagram was used to filter the 98 hub genes found in the key module with the 1045 DEGs. We identified 18 hub genes from this process, 9 of which were found to be correlated with MLL-r status, using the UCSC Xena analysis. By using RT-qPCR, we validated these 9 hub key genes to be upregulated in the MLL-r ALLs (RS4;11 and SEM) compared to the non-MLL-r ALL (RCH-ACV) cell lines. Three of these genes, BCL11A, GLT8D1 and NCBP2, were shown to be increased in MLL-r ALL patient bone marrows compared to the non-MLL-r ALL patient. Finally, Kaplan-Meier analysis indicated childhood ALL patients with high BCL11A expression had significantly poor overall survival. Conclusion These findings suggest that upregulated BCL11A gene expression in childhood ALLs may lead to MLL-r ALL development and BCL11A represents a new potential therapeutic target for childhood MLL-r ALL.